Production planning optimization using linear goal programming method (a case study in UD. Koing) - Marni Astuti; Suhanto Suhanto; Renaldy Setya Utomo (Compiler, 2021)
Small Medium Enterprise (SME) industry hold significant role in economic development. In order to be competitive in competition, industry is demanded to be able to make optimum production plan for fulfilling the customer needs. UD KOING as one of product made based skin manufacture companies from time to time is demanded to maximize profit production-target volume, formulating model problems and optimization of raw material. The purpose of this research is that the company gets output according to consumer demand which minimizes production costs and maximizes profits. To answer all those challenges, this research applied goal programming method, where this method can achieve more than one goal only. Based on the data processing, the company target can be achieved through the company profit IDR 7,089,620 compared to the realization of IDR 7,052,410. The total production cost is IDR 16,635,380 compared to realized production cost of IDR 16,554,590 by producing wallet with the number 51 pieces, purse 9 pieces, nametag 13 pieces, pouch 15 pieces and necklace 14 pieces.